Analysis of Symmetric and Asymmetric Multilevel Inverter Topologies with Focus on THD Performance - Mohamed Sani, Muhammad Syazani Abid; Putra Nur Danish Nur Mizhuari; Muhammad Muddassir, Muhammad Aiman; Abu Bakar , Afarulrazi; Ponniran, Asmarashid (Journal of Electronic Voltage and Application, 2026)
Inverters are important components in modern power conversion systems, including renewable energy applications and electric vehicles, where the conversion of DC power to high-quality AC output is essential. With the growing demand for power quality, minimizing Total Harmonic Distortion (THD) is crucial, as high levels can degrade system performance and cause equipment failure. This project aims to simulate and compare symmetric and asymmetric cascaded H-bridge (CHB) multilevel inverters to determine the most efficient topology for power electronics applications. The study involves developing separate PLECS models for a 5-level symmetric and a 7-level asymmetric CHB inverter, implementing Sinusoidal Pulse Width Modulation (SPWM) and Level-Shifted SPWM (LSSPWM), respectively, and applying an LCL filter to the output of each. The results show that the unfiltered THD for the symmetrical 5-level inverter was 27.00%, which was reduced to 0.13% after LCL filtering. The asymmetrical 7-level inverter inherently performed better, with an initial THD of 17.42% that improved to 4.38% after filtering. These findings conclude that both inverter designs, particularly the asymmetric topology with their finer voltage steps, effectively meet harmonic standards below the required 5% threshold after filtering, validating their suitability for real-world systems.